2019
DOI: 10.3390/ijerph16132259
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Carbonaceous Components in PM2.5 on Pulmonary Function: A Panel Study of 37 Chinese Healthy Adults

Abstract: Objectives: To explore the health effects of indoor/outdoor carbonaceous compositions in PM2.5 on pulmonary function among healthy students living in the local university campus. Methods: Daily peak expiratory flow (PEF) and forced expiratory volume in 1 second (FEV1) were measured among 37 healthy students in the morning and evening for four two-week periods. Concurrent concentrations of indoor and outdoor PM2.5 (particulate matter with an aerodynamic diameter ≤ 2.5m), carbonaceous components in PM2.5, ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A major strength of this study was that we obtained a large number of daily PEF measurements over three years in the spring, while most previous panel studies investigating the associations with PM 2.5 exposures have been designed to collect lung function measurements over multiple days or a few months [ 24 , 29 32 ]. The large number of PEF measurements in our study could increase the statistical power to detect a smaller effect size for the exposure-response associations among children with asthma, who are one of the most vulnerable populations to air pollution exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of this study was that we obtained a large number of daily PEF measurements over three years in the spring, while most previous panel studies investigating the associations with PM 2.5 exposures have been designed to collect lung function measurements over multiple days or a few months [ 24 , 29 32 ]. The large number of PEF measurements in our study could increase the statistical power to detect a smaller effect size for the exposure-response associations among children with asthma, who are one of the most vulnerable populations to air pollution exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of this study was that we obtained a large number of daily PEF measurements over three years in the spring, while most previous panel studies investigating the associations with PM 2.5 exposures have been designed to collect lung function measurements over multiple days or a few months [24,[29][30][31][32]. The large number of PEF measurements in our study could increase the statistical power to detect a smaller effect size for the exposure-response associations among children with asthma, who are one of the most vulnerable populations to air pollution exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently many studies have been reported regarding the carbonaceous component of ambient particulate matters (PMs) and their harmful effects on human health and environments such as climate and visibility [1][2][3][4]. It is commonly classified into two main fractions, i.e., organic carbon (OC) and elemental carbon (EC).…”
Section: Introductionmentioning
confidence: 99%